Marketing communication efficiency: challenges and opportunities in not-for-profit sector - Sharma, Piyush (2019)
In this talk, Professor Sharma would use his research on marketing communication effectiveness to identify the challenges and opportunities faced by not-for-profit sector in using popular marketing concepts and principles in their everyday operations. First, he would introduce six key concepts related to marketing communication effectiveness, a) scarcity effect in advertising, b) first vs. third person effects in advertising, c) message framing and advertising appeals, d) celebrity endorsements, e) neuroscientific methods to evaluate advertising effectiveness, and f) sharing of viral advertisements. Next, he would discuss the implications of all these concepts in the context of not-for-profit organisations and social marketing. Finally, he would layout a road-map that not-for-profit organisations could use to develop, implement and monitor effective marketing communications.